Effectiveness of comprehensive hand hygiene module on preschool children in Klang Valley, Malaysia - Mohd Rani, Mohd Dzulkhairi; Mohamed @ Abd Aziz, Nurul Azmawati; Tengku Jamaluddin, Tengku Zetty Maztura; Ismail, Zarini; Ramli, Shalinawati; Faroque, Habibah; Abd Samad, Farishah Nur; Ariffien, Abdul Rasyid; Che Amir Farid, Aisyah Ar Redha; Isahak, Ilina (Korean Pediatric Society, 2020)
Preschool children are exposed to infectious diseases such as hand, foot, and mouth disease and colds due to their close relationship with other children at school and their weak immune systems. It has been proven that proper hand hygiene practices can curb the risk of developing these illnesses. This effectiveness study aimed to test a hand hygiene module developed for preschool children at 2 public preschools owned by Majlis Agama Islam Wilayah Persekutuan in Klang Valley, Malaysia. A total of 356 children were involved in this study; of them, 49% were boys, 45.2% were 5 years old and the rest were 6 years old.